THE INFLUENCE OF EMPLOYER BRANDING, WORK EXPECTATIONS, AND CORPORATE REPUTATION ON INTENTION TO APPLY FOR A JOB AMONG FINAL-YEAR MANAGEMENT STUDENTS AT THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MALIKUSSALEH - Shadaqta Amalia; Khairawati; A Hadi Arifin; Sullaida (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study is to analyze the influence of employer branding, work expectations, and corporate reputation on Intention to Apply for a Job among final-year students in the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The study was conducted on final-year students in the 2022 intake of the Management Study Program, Faculty of Economics and Business, Malikussaleh University. The research method used a quantitative approach, distributing questionnaires to 175 final-year student respondents. Data analysis was performed using the Partial Least Squares (PLS) method with the assistance of the SmartPLS application. The results showed that employer branding had a positive and significant effect on Intention to Apply for a Job, work expectations had a positive and significant effect on job application intentions, and corporate reputation had a positive and significant effect on Intention to Apply for a Job. These findings indicate that employer branding, work expectations, and corporate reputation are important factors that can encourage increased Intention to Apply for a Job, particularly in the decision-making process of applying to a company.